Rethinking Literature Reviews: Key Pitfalls and Strategies for Postgraduates - Willie, Michael Mncedisi (DAS Institute, 2025)
The literature review was a fundamental component of postgraduate research, but it was often misinterpreted and underused as a vital tool for critical analysis. This study explored common pitfalls encountered by postgraduate students in constructing literature reviews, including over-reliance on descriptive summaries, thematic fragmentation, outdated sourcing, and insufficient synthesis across studies. Through a qualitative content analysis of peer-reviewed guidelines and academic writing literature, key themes emerged that emphasised the importance of thematic organisation, critical engagement with current and high-quality sources, explicit identification of knowledge gaps, and consistent alignment with research questions. The findings highlighted the need to integrate conceptual and theoretical frameworks as intellectual scaffolding and to promote reflexivity to enhance scholarly rigour. This study offered practical recommendations for postgraduate researchers to transform the literature review from a mere summary into a compelling, theory-informed argument that effectively justified the relevance and originality of their research.